2022
DOI: 10.1111/grs.12385
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Italian ryegrass (Lolium multiflorum Lam.) regrowth via inoculation with an ammonia‐oxidizing bacterial strain

Abstract: This study aimed to investigate the effect of a soil ammonia‐oxidizing bacterial (AOB) strain on Italian ryegrass (Lolium multiflorum Lam.) regrowth. Potted Italian ryegrass was used as test material. We isolated and screened an AOB strain from the soil for use in inoculation of other soils to increase nitrification. The sequence of the two isolated and screened AOB strains (S2_8_1 and S2_7_25) were 100% similar to that of Ensifer sesbaniae and Acinetobacter pittii. The nitrification inhibitor 3,4‐dimethylpyra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Previous studies primarily focused on their vital role in nitrification processes within aquatic and soil environments ( Taylor et al, 2009 ; Kouki et al, 2011 ; Matsuno et al, 2013 ; Soliman and Eldyasti, 2018 ; Fang et al, 2019 ). A limited body of research has revealed that HAOB strains promote soil nitrification in the rhizosphere, leading to the release of nitrate nitrogen from the soil ( Wu et al, 2022 , 2023 ). However, our study introduces a novel perspective by exploring their role in enhancing plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies primarily focused on their vital role in nitrification processes within aquatic and soil environments ( Taylor et al, 2009 ; Kouki et al, 2011 ; Matsuno et al, 2013 ; Soliman and Eldyasti, 2018 ; Fang et al, 2019 ). A limited body of research has revealed that HAOB strains promote soil nitrification in the rhizosphere, leading to the release of nitrate nitrogen from the soil ( Wu et al, 2022 , 2023 ). However, our study introduces a novel perspective by exploring their role in enhancing plant growth.…”
Section: Discussionmentioning
confidence: 99%